STRUKTUR KOMUNITAS MAKROZOOBENTOS DI KAWASAN REHABILITASI MANGROVE DAN MANGROVE ALAMI DI KAMPUNG NIPAH KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Rabiah Rabiah; E. Harso Kardhinata; Abdul Karim (Universitas Medan Area, 2017)
Research on the community structure of macrozoobenthos in the area of mangrove rehabilitation and mangrove naturally in Kampung Nipah Bedagai Serdang, North Sumatra was aim to determined the community structure of macrozoobenthos with the inventory and identification of the types of macrozoobenthos at the sites. The method used in this research is descriptive method by determining and manufacture of sampling points with purposive sampling method. The results showed that macrozoobenthos were found grouped in three classes of Bivalves, Gastropods, and Polychaeta with the total number of individuals as much as 775 individuals. Group class that has the number of families and the highest number of species are Gastropods (19 families and 29 species), followed by Bivalves (6 families and 13 species). Polychaeta only has one family and one spesies. Diversity index (H ') of the study sites showed a value of 2.37 with the medium category. Value uniformity among the sites is 0,63 which means that the distribution of individuals of each type tends to evenly at each station and observation points.